Development of an international online learning platform for hepatopancreatobiliary surgical training: a needs assessment. Issue 12 (24th June 2014) - Warner, Susanne G.; Connor, Saxon; Christophi, Christopher; Azodo, Ijeoma A.; Kent, Tara; Pier, David; Minter, Rebecca M.
Abstract: Background: The Americas Hepato‐Pancreato‐Biliary Association (AHPBA) and the Australian and New Zealand Hepatic, Pancreatic and Biliary Association (ANZHPBA) are developing an online distance learning curriculum to facilitate an interactive didactic experience for hepatopancreatobiliary (HPB) fellows in the operationalization of existing HPB fellow curricula. Two needs assessment surveys were carried out to identify the optimal structure and process for deployment in fellow education. Methods: A 22‐question survey querying fellows' learning styles and current and anticipated use of learning tools was disseminated electronically to 38 North American and Australasian HPB fellows. A follow‐up 20‐question survey was administered to assess fellows' feelings regarding online content. Results: Response rates were 55% ( n = 21) for the first survey and 42% for the second ( n = 16). In the first survey, 67% of respondents claimed familiarity with the required HPB curriculum, and 43% indicated dissatisfaction with current personal study strategies. A total of 62% ( n = 13) reported studying with focused clinical relevance versus using a prescribed curriculum ( n = 1, 5%). Fellows anticipated participating using online tools once ( n = 10, 48%) or two or three times ( n = 5, 24%) per week. Most respondents ( n = 18, 86%) would meaningfully follow one or two discussions per month. The second survey identified themes for improvement such as discussion topics of interest, avoidance of holiday timing and mandatory participation. Conclusions: An international online distance learning format is an appealing mechanism for improved dissemination and operationalization of the established HPB fellow curricula. Fellows will engage in interactive discussions monthly. Controversial topics or those requiring complex decision making are best suited to this learning format.